Clerodane Diterpenoids with Anti-hyperglycemic Activity from Tinospora crispa - Gao, Yuan (Nat Prod Bioprospect, 2016)
ABSTRACT: Four new clerodane diterpenoids, tinosporols A–C (2–4) and tinosporoside A (5), together with six known analogues were isolated from the vines of Tinospora crispa. Their structures were established by extensive spectroscopic analysis. The relative configuration at C-12 in the known diterpenoid borapetoside E (1), the major component of the plant, was firstly established with the aid of molecular model. Compound 1 significantly reduced serum glucose levels at dose-dependent manners in alloxan-induced hyperglycemic mice and db/db type 2 diabetic mice. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-016-0109-3) contains supplementary material, which is available to authorized users.